2019
DOI: 10.3390/su11102865
|View full text |Cite
|
Sign up to set email alerts
|

Firm Growth and R&D in the Korean Pharmaceutical Industry

Abstract: We explore the impact of research and development (R&D) on sales growth rate with firm-specific factors under the Korean pharmaceutical industry structure using listed Korea pharmaceutical company data from 2007 to 2018 with the quantile regression technique. We find that R&D intensity has a positive effect on firm growth rate while R&D scale a negative effect on the firm growth rate at the upper quantile, whereas the result is opposite at the lower quantile. Firm size has a mixed relationship with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 74 publications
(97 reference statements)
0
17
0
Order By: Relevance
“…The R&D investments of biopharmaceutical companies are determined according to their spatiotemporal context and individual factors. At the company level, the size of an enterprise often has a significant influence on its R&D investment (Chung et al, 2019;DiMasi, 2014;Philippe et al, 2013). Other factors at the company level include company sales (Prentis et al, 1988), company earnings (David et al, 2009), corporate governance structure (Jing & Gou, 2010), tax burden (William & McCutchen, 1993), and labor costs (Omta et al, 1994).…”
Section: Spatial Competition Of Biopharmaceutical Randdmentioning
confidence: 99%
See 1 more Smart Citation
“…The R&D investments of biopharmaceutical companies are determined according to their spatiotemporal context and individual factors. At the company level, the size of an enterprise often has a significant influence on its R&D investment (Chung et al, 2019;DiMasi, 2014;Philippe et al, 2013). Other factors at the company level include company sales (Prentis et al, 1988), company earnings (David et al, 2009), corporate governance structure (Jing & Gou, 2010), tax burden (William & McCutchen, 1993), and labor costs (Omta et al, 1994).…”
Section: Spatial Competition Of Biopharmaceutical Randdmentioning
confidence: 99%
“…The second part is the variables of biopharmaceutical companies. The company's size has a significant impact on the R&D expenditure of biopharmaceutical enterprises (Chung et al, 2019;DiMasi, 2014). In this study, two variables, the logarithm of total assets (InTA) and the logarithm of total employees (lnTE), are used to measure the size of biopharmaceutical enterprises.…”
Section: Variable Measurementmentioning
confidence: 99%
“…In addition to both China and Bangladesh, a study conducted in Korea by Chung et al (2019) on firm growth and research initiatives in the Korean pharmaceutical industry showed that mix relationship exists between sales and research depending on firm size. It should be noted that there are no studies to date that show CSR activities have a negative relationship with organizational performance in the pharmaceutical sector.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…Empirical studies which extended the regression model of Gibrat's law (1931) by considering additional determinants for firm growth along with R&D expenditure have included firms from various industries demonstrating considerable heterogeneity in R&D intensity, innovation persistence and size. Having found R&D as a critical driver of firm growth (Chung et al, 2019), many researchers studying firm growth have included R&D in the list of independent variables. Coad et al (2016) and Goedhuys and Sleuwaegen (2015) found that in younger firms, R&D had a significant effect on performance in the upper growth quantile and a negative effect at lower growth quantile.…”
Section: Resource-based Viewmentioning
confidence: 99%